Strategi Mengantisipasi Politik SARA pada Pemilu melalui Pendidikan Politik - Widiatmaka, Pipit; Yuliandari, Erna (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
West Kalimantan Province is one of the locations where ethnic and religious disputes frequently occur, as the rise of the SARA issue in recent elections has exacerbated the situation. The goal of this research is to determine the role of political education, the phenomenon of political education in West Kalimantan Province, strategies for anticipating the SARA issue in West Kalimantan Province elections, and the implications for harmony among differences in West Kalimantan Province. Literature was used as the qualitative strategy and research type. Data gathering strategies include documentation studies, as well as data analysis via content analysis.Assume the people of West Kalimantan have political literacy. In that situation, they should expect ethnic and religious disputes to have an impact on national and state peace. They will increase the quality of West Kalimantan's secret, open, honest, and fair elections. The inhabitants of West Kalimantan aspire to a pleasant and harmonious living free of SARA concerns and background distinctions. Keywords: Racial Politics; Elections; Political Education